Longitudinal hydration assessment in collegiate basketball players over various training phases - Heishman, A. D.; Daub, B. D.; Miller, R. M.; Freitas, E. D.; Bemben, M. G. (The Journal of Strength and Conditioning Research, 2021)
To the best of our knowledge, previous literature has not longitudinally examined hydration status in collegiate basketball players. Therefore, the purpose of this investigation was to examine the prepractice hydration status of collegiate basketball players across various training phases for 2 consecutive years. Retrospective analyses examined prepractice urine-specific gravity (USG) assessments obtained from National Collegiate Athletic Association (NCAA) Division I male basketball players during the preseason and competitive season, for 2 consecutive years. The first year (year 1 = Y1) of analysis consisted of 15 athletes and the second year (year 2 = Y2) consisted of 16 athletes, with 8 athletes in both seasons. Hydration status was classified based on the National Athletic Trainers' criteria: (a) euhydrated, USG < 1.020; (b) hypohydrated, USG = 1.020-1.030; and (c) significantly hypohydrated, USG > 1.030. Additional comparisons examined the association of minutes played with hydration status and changes in hydration status for athletes returning from Y1 to Y2. The results indicated 55-65.7% of cases showed levels of significant hypohydration during the preseason and competitive seasons for both years. Preseason hydration status was significantly better than the competitive season (Y1, p = 0.008; Y2, p = 0.005). Despite significant differences in minutes played (p < 0.001), no differences in hydration status were observed. Returning athletes displayed no differences in hydration status between Y1 and Y2. Collegiate basketball players show levels of hypohydration when longitudinally examined across various training phases. Although hydration may be improved in the preseason, alternative factors such as average game minutes played and length in program may not influence hydration status.